PARENTING ISLAMI : PERAN ORANG TUA TUNGGAL DALAM MENANAMKAN SIKAP MANDIRI DAN BERTANGGUNG JAWAB PADA ANAK USIA DINI - Rambe, Aisyah Putri; Dinil Arifah Nasution; Nurul Azmi Pasaribu; Masganti Sitorus (LPPM IAD Probolinggo, 2024)
This study investigates the function of single parents in forming discipline and a sense of responsibility in young children in Dusun IV Laut Dendang. This study uses a qualitative method with a descriptive approach. Information was collected through in-depth interviews with single parents. The results of the study revealed that single parents face various difficulties, such as meeting the needs of children in terms of physical, emotional, and financial. However, by implementing Islamic parenting patterns based on the values ​​of the Qur'an and Hadith. Children are taught to carry out daily tasks independently, such as tidying up toys, eating by themselves, and recognizing the importance of responsibility in everyday life. Religious education is also an important foundation in forming a child's character that is strong, independent, and responsible. Keywords: Islamic parenting, single parents, independence, responsibility, early childhood.